EFFECTIVENESS OF EARLY REHABILITATION IN PATIENTS WITH ACUTE ISCHEMIC STROKE IN NEUROLOGY UNIT - O. I. Kolenko; I. O. Chemerys; I. V. Chernetskyi (Eastern Ukrainian Medical Journal, 2020)
Introduction. The theoretical grounding and solution of the scientific problem, which consist in the study of factors that contribute to the improvement of patients with ischemic brain stroke rehabilitation, are presented in this paper; it is a study of modern methods of rehabilitation and their effectiveness. The objective of the study was to find out reasons why the conducted research shows the significant importance of the use of kinesitherapy, transcutaneous electrical nerve stimulation, and psychotherapy in the system of early rehabilitation of patients. Based on the study, we established that lateralization of brain lesions is an important factor that affects the rehabilitation potential of patients. The signs of motor impairment and cognitive deterioration in patients with ischemic stroke requires the development of individual and intensive rehabilitation measures in order to restore brain function, and adequate treatment of all possible manifestations that impair the effectiveness of rehabilitation and the quality of patients’ life after ischemic stroke. In addition, our task was to study the incidence of post- stroke depressive disorders and their relationship with psychosocial factors. Material and methods. The empirical part was performed by collecting information about 60 patients who were treated and had initial rehabilitation in the early recovery period in the stroke unit. Patients were divided into 2 groups according to the timing of recovery to assess the likelihood of post-stroke depression and recovery against time. The analysis of data obtained after processing of materials was carried out using Microsoft Excel’16 program. Statistical processing of the results was carried out by the method of variational statistics using the Student’s test. The data were collected from patients with cerebral circulation disorders of Communal Institution in neurology unit of Sumy City Council “City Clinical Hospital No.4”. Study results: It was established that gender is not a determining factor in the recovery of patients after ischemic stroke and does not significantly impact the rehabilitation prognosis. The most effective factors in recovering lost functions and skills after an ischemic stroke were complexity, phasing, and early start of rehabilitation measures. Post-stroke depression is a common consequence of ischemic stroke and 54 (90 %) patients (p < 0.05) have it. The characteristic feature of depression in post-stroke patients was the persistence of symptoms, mild and moderate degree of severity, criticism of their condition, etc. Depressive disorders were complex, polymorphic, and included signs of both organic depression and personal response to the development of brain damage. The relationship of depression with the severity of neurological deficits, localization of the focus, as well as with psychosocial factors such as lonely living, loss of work, high social and professional status were shown. Further study of cognitive impairment and the role of specialists in solving the problem of their correction are required. Thus, a complete clinical-neurological and rehabilitation characteristic of patients with different baseline data and conditions is given, based on the results of our own research